The Fiery Holy Spirit : The Spirit's Relationship with Judgment in Luke - Acts - Kienzler, Jonathan, (Journal of Pentecostal Theology Supplement Series ;, 2015)
The baptism with the Spirit and fire has been a major area of study by theologians and has been pursued by the historical church seeking God's holiness and power; yet its relationship to judgment has often been ignored. This book explores the Holy Spirit's relationship with judgment in Luke-Acts through seven texts: Luke 3:16-17; 12:8-10; Acts 5:1-11; 7:51; 8:18-23; 13:9-11; 28:25-28. In these texts, the Holy Spirit is connected with fire, unforgiveness, deception, resistance, greed, blindness, or condemnation. In each instance, Luke's presentation is examined to determine the Spirit's role in the process of judgment. Through the Spirit, Jesus judges, cleanses, purges, and divides his people from the world. Luke portrays the Spirit as the executive power of Jesus' reign as judge, exposing, opposing, and condemning those who reject the gospel.